Global burden of breast cancer and application of patient-reported outcomes in clinical trials: a systematic analysis based on the global burden of disease study 2021 and WHO international clinical trial register database - Hao, Jiaxin; Gong, Yijia; Zhang, Xiaowen; Du, Minghong; Wang, Huan; Guo, Guolin; Zhou, Mengqing; Tian, Tian; Rong, Hongguo (Frontiers in Oncology, 2025)
BackgroundBreast cancer is one of the most prevalent tumors worldwide, significantly compromising the survival and quality of life of patients. This study aims to evaluate the global burden and the application of patient-reported outcomes (PROs) in clinical trials of breast cancer.MethodsData of breast cancer burden is extracted from the Global Burden of Disease Study (GBD) 2021 database. This study analyzes geographic patterns, temporal trends and age patterns of female breast cancer disease burden globally and explored the association between age standardised rates for disability adjusted life years (ASDR) of female breast cancer and sociodemographic index (SDI). The interventional clinical trials of breast cancer are selected in the WHO International Clinical Trial Register database from January 1, 2010, to December 31, 2022. The application of PROs is classified into three categories: 1) precisely listed PRO instruments as outcomes, 2) mentioned patient subjective feelings without clarifying specified PRO instruments, and 3) not mentioned any PROs as outcomes.ResultsGlobally, in 2021 the age standardised rates for point prevalence of female breast cancer per 100000 population was 450.64 (427.02 to 475.96), the age standardised rates for incidence (ASIR) per 100000 population was 46.40 (43.26 to 49.56), and the ASDR per 100000 population was 455.56 (426.64 to 485.30). Compared with 1990, the ASIR of female breast cancer in 2021 had increased while the ASDR had decreased globally. Trials involving PROs only account for 37.87% (3968/10478). The Visual Analog Scale and Cancer Quality of Life Questionnaire-Core 30 are the most common instruments in these trials.ConclusionsThe disease burden of breast cancer is severe and varied worldwide while the application of PROs in clinical trials remains noteworthy. Increasing population awareness about policy for breast cancer care and the application of specific PRO instruments is warranted to reduce the future burden of disease.